Metabolic syndrome in rural Kerala: a hospital based study - Srinivasan, Shuba; Lingegowda, Jyothi B.; Rajan, Chinnappa; Muddegowda, Prakash H.; R., Ramkumar Kurpad (International Journal of Advances in Medicine, 2016)
Background: Metabolic syndrome refers to a cluster of various interrelated cardio-metabolic risk factors that promote the development of atherosclerotic cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). Identifying at risk individuals is necessary for early medical management, thereby reducing the economic burden on the patient and the society. The objective of this study was to assess the prevalence of metabolic syndrome in patients presenting to medicine clinics of our institute. Methods: This cross-sectional hospital based study was carried out at department of medicine, DM Wayanad institute of medical sciences, Wayanad, Kerala and included 432 patients attending the general medicine outpatient department. Patients’ demographic details and anthropometric measurements including height, weight, waist and hip measurements were taken. Clinical data including blood pressure, blood sugars and fasting lipid profile was also collected. The NCEP ATP III (National cholesterol education program - adult treatment panel III) criteria for diagnosis of metabolic syndrome were used to make a diagnosis of metabolic syndrome. Results: On applying the modified NCEP ATP III guidelines with the waist circumference specific to Asian population, we found that the prevalence of metabolic syndrome in our study population was 60.9%. The prevalence was more in females than in males and the difference was statistically significant (p = 0.049). Abdominal obesity and decreased HDL was more in females as compared to males and the difference was also found to be statistically significant. 27% of the study population with metabolic syndrome was normal or underweight. Conclusions: The prevalence of metabolic syndrome in the present studied population was high as they represent patients presenting to hospital. This data is more like the tip of an iceberg. Larger population based studies and intervention in the form of aggressive lifestyle modification is the need of the hour to prevent the cardio-metabolic complications of metabolic syndrome.